The Effectiveness of the Problem Based Learning Model Using Lift The Flap Book Media in Post Pandemic Biology Learning - Ainun Aziza; Nirwana Anas (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
After the COVID-19 pandemic, changes in the environment and learning conditions are interesting to be studied and used as a means of evaluating learning. Social activity in society began to return to normal, including education. The purpose of this study is to determine the impact that post-pandemic education has on biology learning outcomes. In the study, Non equivalent control group design was used. There were 25 students in each of the two sample classes. The media for the experimental class is class XI IPA 3, which uses the Problem Based Learning Lift learning model. Instead, the control class uses conventional learning strategies XI Science 1. The written research instrument totals twenty multiple-choice questions. The T-test is performed after collection from the data. The findings show that the Lift The Flap Book media and the Problem Based Learning learning model affect students' biology learning success. Teachers can use the Problem Based Learning learning model.  A learning model to improve the biology learning outcomes of its students. Teachers can more easily distribute biology learning materials by utilizing the Lift The Flap Book media so that the learning process runs smoothly and effectively